Ryōgen and Mount Hiei : Japanese Tendai in the tenth century - Groner, Paul, 1946- (Studies in East Asian Buddhism ;, 2002)
"Ryogen and Mount Hiei focuses on the transformation of the Tendai school from a small and impoverished group of monks in the early ninth century to its emergence as the most powerful and influential school of Japanese Buddhism in the last half of the tenth century - a position it would maintain throughout the medieval period. This is the first study in a Western language of the institutional factors that lay behind the school's success. At its core is a biography of a major figure who played an active role during the transformation, Ryogen (912-985). The discussion, however, extends well beyond a simple biography as Ryogen's activities are placed in their historical and institutional context."--Jacket